Paying Homage: The Participation of Guild Confraternities in Archiepiscopal Entries into Tarragona - González, Sergi González (Confraternitas)

(untitled) (Iter Press, 2020)
The original significance of the public entry of a new archbishop into Tarragona lies in the fact that the city, through its confraternities, honoured one of its social elite with a popular celebration. Urban government was based upon two authorities: the king and the archbishop. In Tarragona, a city of deeply rooted customs and traditions, the entry ritual remained almost unchanged from medieval times to the modern era. Guild confraternities were active participants in urban ritual, with their dances, figures, and fantastic animals, and thus created a nexus of identity among the urban community as a whole. Detailed descriptions in municipal chronicles make it possible to study which confraternities existed in Tarragona, and in what ways they participated in the festive celebrations and were connected to the social network, as, for a brief moment, they enjoyed an activity far removed from the daily grind of work. The aim of this article is to observe how the ecosystem of guild confraternities in Tarragona varied little over time, how they always participated with the same dance and, as a result, how the soundscape of those dances became a characteristic soundmark of urban ceremony there.